The Improvement Of Menu Based On Pare As A Diet Menu Specially In Diabetes Mellitus Patients In Hospitals - Ria Setyawati; Praseptia Gardiarini (Program Studi Tata Boga Universitas Negeri Jakarta, 2019)
Background: Diabetes Mellitus (DM) is a disease whose prevalence has increased every year. The increase in prevalence is thought to be due to lifestyle changes and urbanization that affect the pattern and selection of food menus. One of the easiest management is to consume drugs, but the use of repentance for a long time will cause side effects and quite expensive costs.Pare is one type of vegetable that can be used as an alternative to the main food menu for diabetic mellitus, but because the taste is bitter, Pare is rarely used as a daily menu. Even at the Hospital a Pare-based menu is rarely applied to patients, especially those with Diabetes. Object: This study aims to examine the development of Pare-based menus so that it can be used as an alternative menu for inpatients in hospitals, especially for people with Diabetes Mellitus. Methods:There are two methods used in this study, experimental research methods and statistical descriptions. Result: The results of the stir-fried bitter melon from the experiment were bitter melon vegetables whose color was fresh green, the distinctive aroma of bitter melon still smelled, the texture was soft and the bitter taste was somewhat reduced. Panelist's hedonic test, who stated that they rather like 6 (18.8%), and like 21 (65.6%) and really like 4 (12.5%). Conclsion: Based on the results of the study, it can be concluded that bitter melon can be a basic menu item for type 2 diabetes mellitus patients hospitalized at the hospital.